Physiological and perceptual demands of singles and doubles beach tennis in women of different competition levels - Jung, Nathalia; Carpes, Leandro; Domingues, Lucas; Abreu, Rodrigo; Mohr, Magni; Ferrari, Rodrigo (Frontiers in Physiology, 2024)
Purpose: To analyzed and compare the physiological responses of women during singles and doubles beach tennis sessions.In this crossover trial, twenty-two women with previous participation in amateur beach tennis tournaments randomly performed two experimental sessions: singles and doubles beach tennis. The routine for both sessions consisted of 10-min of seated rest, followed by 45-min of beach tennis and 30-min of post-exercise recovery. Participants were matched against opponents of the same competition level, defined according to their local beach tennis ranking (advanced or intermediate level). They warmed up with basic techniques for 5-min and played 3 matches lasting 12-min, interspersed with 2-min recovery intervals. Heart rate (HR), energy expenditure (EE), number of steps (STEPS), handgrip strength (HS), rating of perceived exertion (RPE), and enjoyment were assessed throughout the sessions. Generalized estimating equations were employed to examine the main effects between experimental sessions over the time and in relation to competition level.Results: HRmean and HRmax (Δ: HRmean=13±3 bpm; HRmax=11±3 bpm) as well as EE andSteps (Δ: EE=66±22 kcal; RPE=2±0 A.U.; Steps=250±52 A.U.) were higher in singles than doubles (P<0.05). The percentage of total time spent in the highest HR zone (91-100%HRmax) was significantly greater in singles than in doubles (39±22 vs. 15±18%; P<0.05). Differences were found in the percentage of total time spent in each HR zone, recovery HR, and HS between competition levels (P<0.05).Singles beach tennis resulted in higher physiological demands than doubles in women, and players' competition level partly affects the training responses.